Development of scientific-based interactive multimedia with polyhedron material - Rosa Fachma Rani; Muhammad Khoiril Akhyar; Nur Fadilatul Ilmiyah; Hatıra Günerhan (Universitas Islam Negeri (UIN) Syekh Wasil Kediri, 2024)
The increasing integration of technology within educational settings underscores a critical need for the development and rigorous validation of digital learning resources capable of enhancing pedagogical effectiveness and fostering meaningful student engagement. This research directly addresses this imperative by detailing the systematic design, meticulous development, and comprehensive evaluation of a scientific-based interactive multimedia tool specifically crafted for the instruction of polyhedron concepts. The researchers used one of R&D (Research and Development) model as development procedures, that is Five steps of the ADDIE development model— Analysis, Design, Development, Implementation, and Evaluation. With an average score of 92.2% from expert material and 87.1% from experts media, these results indicate that the designed product is valid. In the product practical test, an average score of 90.2% was obtained, which shows that the product produced is practical. The n-gain formula is used to determine the product effectiveness. Based on this test, the results obtained were 0.67 in small scale testing and 0.64 in large scale testing. Both of the results are included in the medium criteria, which means that the product developed is quite effective. The study's findings demonstrate that the created products are of excellent quality, can be effectively used to enhance learning, and get positive feedback from students.